Silencing of the Long Non-Coding RNA TTN-AS1 Attenuates the Malignant Progression of Osteosarcoma Cells by Regulating the miR-16-1-3p/TFAP4 Axis - Meng, Xianghai; Zhang, Zhenjun; Chen, Lin; Wang, Xi; Zhang, Qingguo; Liu, Shuheng (Frontiers in Oncology, 2021)
Objectives: Osteosarcoma (OS) is a type of bone malignancy. This study attempted to explore the effect of long non-coding RNA TTN-AS1 (TTN-AS1) on OS and to determine its molecular mechanisms. Methods: The expression of TTN-AS1, microRNA-16-1-3p (miR-16-1-3p), and transcription factor activating enhancer binding protein 4 (TFAP4) in OS was assessed using qRT-PCR. The OS cell proliferation, migration, and invasion were measured using 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), wound-healing, and transwell assays. N-cadherin and MMP-2 protein level was determined with western blot. Interactions between TTN-AS1 and miR-16-1-3p or TFAP4 and miR-16-1-3p were confirmed using the dual-luciferase reporter assay. Additionally, an OS xenograft tumor model was constructed to assess the effect of TTN-AS1 on tumor growth. Results: TTN-AS1 and TFAP4 expression was increased in OS, while miR-16-1-3p expression was decreased. TTN-AS1 silencing restrained OS cell proliferation, migration, invasion, N-cadherin and MMP-2 protein expression, and hindered tumor growth. MiR-16-1-3p overexpression retarded the malignant behavior of OS cells. TTN-AS1 played a carcinostatic role by down-regulating miR-16-1-3p in the OS cells. Moreover, miR-16-1-3p inhibition or TFAP4 elevation weakened the suppressive effect of TTN-AS1 silencing on OS cell tumor progression. Conclusion: TTN-AS1 promoted the proliferation, migration, invasion, and epithelial-mesenchymal transition (EMT) of OS cells via mediating the miR-16-1-3p/TFAP4 axis. TTN-AS1 may be a critical target for improving OS.